KEANEKARAGAMAN Begonia (BEGONIACEAE) DARI KAWASAN GUNUNG WATUWILA DAN GUNUNG MEKONGGA, SULAWESI TENGGARA - Deden Girmansyah (BERITA BIOLOGI, 2010)
A taxonomic study of the genus Begonia Blume (Begoniaceae) in South East Sulawesi (Mt. Mekongga and Mt. Watuwila) were conducted based on morphological characters. Six species of Begonia were discovered. Three previously known species (Begonia aptera Blume, B. flacca Irmschr. and B. hispidissima Warburgh.), two new species and one variety were proposed and on going for publication. Some colour pictures were displayed and potential uses of each species are presented.